Climate change and vulnerability of the pistachio and almond crops in the Mediterranean arid areas - Ghrab M.; Ben Mimoun M.; Masmoudi M.M.; Ben Mechlia N. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Almond and Pistachio are the most important nut crops in Tunisia. The main production areas are located in the central and southern part of the country, characterized by scarce precipitations and harsh environments. Low and highly variable yields are commonly observed under those conditions. Nut crops are reported to be vulnerable to temperature fluctuations and decreasing water availability. In this study, yield response of almond and pistachio to global warming is evaluated under the arid conditions of Tunisia. The approach is focussing on chilling and its incidence on yield, using various chilling accumulation models. On the basis of 35 years of daily climatic data (1980-2014), results show a declining trend in winter chill units. Pistachio yields varied between 0 and 35 kg/tree and were affected by chill accumulation. Yields for three almond cvs varied within similar ranges but seemed to be less affected by warm winters, whereas one variety seemed to be non responsive to chill conditions, probably because of high sensitivity to rainfall variations. With the prospects of global warming, increasing temperatures are expected to be detrimental to nut cultivation in arid Tunisia; unless efforts are deployed to grow the appropriate cultivars.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)